Effects of curing temperature on pull-out behavior and stiffness evolution of epoxy adhesives for NSM-FRP applications - Benedetti, Andrea (2015)
The efficiency of the FRP-concrete strengthening system is strongly influenced by the mechanical properties of the epoxy adhesive, which depend on the curing temperature.In the present work, the influence of temperature on the curing process of the epoxy was examined. Two different temperatures were studied: 20 and 30 °C. The elastic modulus of the adhesive was continuously monitored by using a variant of the classical resonant frequency methods, called EMM-ARM (Elasticity Modulus Monitoring through Ambient Response Method). A simultaneous study of direct pull-out tests with concrete specimens strengthened with NSM carbon FRP laminate strips was carried out at the same two different temperatures to compare the evolution of bond performance with the E-modulus of epoxy since early ages. The results showed that increasing the curing temperature significantly accelerated both the curing process of the epoxy adhesive and the evolution of bond performance. Moreover, the EMM-ARM technique revealed its ability in clearly identifying the hardening kinetics of epoxy adhesives, allowing measurements since very early ages and in different environmental conditions.